The Effect of Foot Angle in Soccer Ball Kick Due to Ball Trajectory - Rubiono, Gatut Rubiono (Universitas Negeri Semarang, 2018)
This study is aims to get the influence of the foot angle in soccer kick on the motion of the ball. The research was carried out by making a leg swing device such as an impact test on material testing. The independent variables include foot angle: 0o (straight to the ball), 25o, and 35o (inner and outer legs) and the angle of swing arm: 45o, 60o, and 75o. The dependent variable is the ball path observed and recorded with the camera. Experimental data was carried out on a cement floor with a length of 5 meters. Five times repetition data collection are done to get the average value. Analysis is carried out to obtain the trajectory characteristics in the form of angles of spherical trajectories. The distance of the trajectory and the time indicated on the recording data is used to calculate the ball velocity. Swing angle data is used to calculate the amount of kick force with the equation of impact energy. The results show that the angle of the foot in the kick of football affects the trajectory of the ball motion. The angle of the foot affects the angle of the ball deviation, the velocity of motion and the energy absorbed by the ball.